Application of Nuclear Analytical Techniques in Elemental Characterization of Wadi El-Nakhil Alabaster, Central Eastern Desert, Egypt - Zain M. Alamoudi; A. El-Taher (Science and Technology of Nuclear Installations)
Instrumental neutron activation analysis (INAA) is a powerful technique for trace element determination in rocks. Nine alabaster samples were collected from Wadi El-Nakhil located at the intersection of lat. 26°10′50′′N and long. 34°03′40′′E, central Eastern Desert, Egypt, for investigation by INAA and Energy Depressive X-Ray Fluorescence (EDXRF). The samples were irradiated by thermal neutrons at the TRIGA Mainz research reactor at a neutron flux of 7 × 1011 n/cm2·s. Twenty-two elements were determined, namely, As, Ba, Ca, Co, Cr, Sc, Fe, Hf, K, Mg, Mn, Na, Rb, U, Zn, Zr, Lu, Ce, Sm, La, Yb, and Eu. The chemical analysis of alabaster indicated having high contents of CaO and MgO and LOI and low contents of SiO2, Al2O3, Na2O, K2O, MnO, and Fe2O3.